Gut Microbiota, Microinflammation, Metabolic Profile, and Zonulin Concentration in Obese and Normal Weight Subjects - Agnieszka Żak-Gołąb; Piotr Kocełak; Małgorzata Aptekorz; Maria Zientara; Łukasz Juszczyk; Gayane Martirosian; Jerzy Chudek; Magdalena Olszanecka-Glinianowicz (International Journal of Endocrinology)
The association between gut microbiota and circulating zonulin level, a marker of intestinal permeability, has not been studied yet. The aim of the study is the assessment of plasma zonulin, haptoglobin and proinflammatory cytokines (TNF-α and IL-6) levels in relation to composition of gut microbiota in obese and normal weight subjects. Circulating inflammation markers, such as TNF-α, sTNFR1, sTNFR2, IL-6, zonulin, and haptoglobin levels were measured and semiquantitative analysis of gut microbiota composition was carried out in 50 obese and 30 normal weight subjects without concomitant diseases. Higher circulating zonulin, TNF-α, sTNFR1, sTNFR2, and IL-6 levels were found in the obese subjects. Plasma zonulin level correlated positively with age (r=0.43, P<0.001), body mass (r=0.30, P<0.01), BMI (r=0.33, P<0.01), fat mass and fat percentage (r=0.31, P<0.01 and r=0.23, P<0.05, resp.). Positive correlations between bacterial colony count and sTNFR1 (r=0.33, P<0.01) and plasma zonulin (r=0.26, P<0.05) but not haptoglobin levels were found. Additionally, plasma zonulin level was proportional to daily energy intake (r=0.27, P<0.05) and serum glucose concentration (r=0.18, P<0.05) and inversely proportional to diet protein percentage (r=-0.23, P<0.05). Gut microbiota-related systemic microinflammation in the obese is reflected by circulating zonulin level, a potential marker of interstitial permeability.